Antecedents of Intention to Buy Non-Muslim Halal Fast Foods: Evidence from the Biggest Muslim Population Country - Muslichah, Istyakara; Ibrahim, Krishnamurti Akbar (Universitas Muhammadiyah Yogyakarta, 2021)
Purpose: This study aims to analyze the antecedents of consumers' intention to buy non-Muslim (Western) halal fast food in Indonesia. Although the country has the biggest Muslim population globally, compared to other countries, Indonesia only managed to get the fourth rank on the overall Global Islamic Economy Indicator score in 2020.Method: This study distributed an online questionnaire, using convenience sampling method, to 159 Muslims in Indonesia. A multiple regression analysis was used to evaluate the proposed relationships of halal awareness, halal certification, halal marketing, religiosity, brand, and food quality towards non-Muslim halal fast food purchase intention.Findings: The results of this study indicate that halal awareness, halal certification, religiosity, brand, and food quality positively influence consumers' intention to buy non-Muslim halal fast food, whereas halal marketing does not support this relationship.Originality: Due to the inconsistent findings from past studies, this study wanted to contribute to the literature about the antecedents of consumers' intention on non-Muslim halal foods in the context of fast foods. Understanding the motivation behind consumers' behavior is also essential for fast food marketers, especially in countries with significant Muslim populations.